1995
DOI: 10.1007/bf00143380
|View full text |Cite
|
Sign up to set email alerts
|

The mobile ferrous iron pool in Escherichia coli is bound to a phosphorylated sugar derivative

Abstract: Based on in vivo Mössbauer spectroscopy it has previously been demonstrated that the intracellular iron pool of Escherichia coli, grown in iron deficient media supplemented with siderophores as the sole iron source, is dominated by a single Fe2+ and a single Fe3+ species. We have isolated the ferrous ion species and have purified it employing native column PAGE, chromatography and ultrafiltration. The purified compound displays an Mapp of 2.2 kDa and an extremely low isoelectric point (pI) of 1.05. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…Such a component has been observed in many bacterial systems. In E. coli, it was shown that this component is located in the cytoplasm and corresponds to an oligomeric ferrous sugar-phosphate complex (6). The second component represents a ferric high-spin species exhibiting Mössbauer parameters similar to those of a variety of bacterial ferritins.…”
Section: Resultsmentioning
confidence: 99%
“…Such a component has been observed in many bacterial systems. In E. coli, it was shown that this component is located in the cytoplasm and corresponds to an oligomeric ferrous sugar-phosphate complex (6). The second component represents a ferric high-spin species exhibiting Mössbauer parameters similar to those of a variety of bacterial ferritins.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA-protecting Dps protein that is ubiquitous in prokaryotes also binds iron (29); however, this functional aspect seems to be more related to the prevention of ROS generation than to a particular role in iron storage (357). The binding component of the intermediary mobile Fe(II) pool in Escherichia coli was found to comprise mainly phosphorylated sugar derivatives containing pentose and/or uronic acid as the major fraction (25). The compound was termed ferrochelatin.…”
Section: ϫ18mentioning
confidence: 99%
“…Magnetite accounted for only 22.2% (ϩFe) and 8.9% (ϪFe) of the intracellular iron pool of RU-1, confirming the reduced magnetite biomineralization in the fur mutant observed by TEM. In all samples, only a small relative contribution came from a ferrous iron high-spin, ferrochelatin-like iron species also found in many bacterial and fungal systems (11). However, while in the WT the ferrous iron high-spin metabolite contributed only 0.35% to the intracellular iron pool, in RU-1 this metabolite was increased to 2% (RU-1 ϩFe) and 1.6% (RU-1 ϪFe).…”
Section: Resultsmentioning
confidence: 86%